Comparation of SAW Method and Topsis in Assesing The Best Area Using HSE Standards - Bendra Wardana; Roni Habibi; M. Harry K Saputra (Politeknik Elektronika Negeri Surabaya (PENS), 2020)
Pertamina Gas is a company engaged in the midstream and downstream industry sectors of Indonesian gas. Currently, the process to access the best areas in PT. Pertamina Gas has not been computerizedand it is still doing manu ally. In assessing the area itself, this method is considered less effective and efficient to determine the best area. Area Assessment according to PT. Pertamina Gas itself is important to iincrease the performance and safety in improving PT. Pertamina Gas Health, Safety, Environment quality. Therefore, we need a system to determine which areas are the best in the PT. Pertamina Gas environment, using predetermined criteria. To create a system commenting on the area in PT. Pertamina Gas Environment, the author used the method Simple Additive Weighting (SAW) and Techniques for Other References With Similarities to Ideal Solutions (TOPSIS) for the best process of conversation and area testing.This study suggests finding the best method for reporting and helping to make decisions based on the best alternative value. The results obtained from this study show that the testing using SAW method is more optimal than using TOPSIS method, with the value of sensitivity change for SAW is 2.4 and TOPSIS is 0.7754.